Neuroprotection by Recombinant Thrombomodulin - Taoka, Yuji; Okajima, Kenji; Uchiba, Mitsuhiro; Johno, Masayoshi (Thrombosis and Haemostasis, 2000)
We examined whether recombinant human soluble thrombomodulin (rhs-TM) reduces compression trauma-induced spinal cord injury through protein C activation in rats. Administration of rhs-TM, either before or after the induction of spinal cord injury (SCI), markedly reduced the resulting motor disturbances. However, neither rhs-TM pretreated with an anti-rhs-TM monoclonal antibody (MAb) F2H5, which inhibits thrombin binding to rhs-TM, nor those pretreated with MAb R5G12, which selectively inhibits protein C activation by rhsTM, prevented the motor disturbances. Intramedullary hemorrhages, observed 24 h after trauma, were significantly reduced in animals given rhs-TM. The increase in the tissue levels of tumor necrosis factor-α (TNF-α), TNF-α mRNA expression, and the accumulation of leukocytes in the damaged segment of the spinal cord were significantly inhibited in animals receiving rhs-TM, but these effects were not observed following administration of rhs-TM pretreated with MAb R5G12 or MAb F2H5. Leukocytopenia and activated protein C all produced effects similar to those of rhs-TM.These findings suggest that rhs-TM prevents compression traumainduced SCI by inhibiting leukocyte accumulation by reducing the expression of TNF-α mRNA and such therapeutic effects of rhs-TM could be dependent on its protein C activation capacity. Findings further suggest that thrombomodulin can be implicated not only in the coagulation system but in regulation of the inflammatory response.
Keywords: Thrombomodulin; spinal cord injury; activated protein C; tumor necrosis factor-α; leukocytes